How do we construct the Actor-Reality Perspective (ARP)? - Ancelin-Bourguignon, Annick (Proceedings of Pragmatic Constructivism, 2013)
The communications presented in Pisa last year variously referred to the perspective which is the focus of the research group. Some of them used it as a global and loose perspective emphasizing the role of actors in constructing their own reality (ARP). Others relied on the Actor-Reality Construction (ARC) model, which investigates this construction in depth. Namely the ARC model postulates that the success of activities operating in a social context depends on the integration of four actor-constructed elements: facts, possibilities, values and communication (Nørreklit, 2011).